Human Development Index, ICT, and Renewable Energy-Growth Nexus for Sustainable Development: A Novel PVAR Analysis - Azam, Anam; Rafiq, Muhammad; Shafique, Muhammad; Yuan, Jiahai; Salem, Sultan (Frontiers in Energy Research, 2021)
The relevance of information and communication technology to long-lasting human improvement cannot be disregarded in this modern world. From this perspective, this study analyzed the association between information and communication technologies, renewable energy, economic growth, and human development indices considering CO2 emissions and remittances from 1990 to 2017 in 30 developing countries by using the panel vector autoregressive (PVAR) model. The findings of the empirical investigation point to the considerable favorable relationship between information and communication technology, renewable energy, and economic growth with the human development index. The causality results suggest that there is bidirectional causality between renewable energy and the human development index. In addition, there is unidirectional causality from human development to information and communication technology. However, the study recommends implementing information and communication technology-related policies to trigger renewable energy for sustainable growth and the human development index.